Behavioral mechanisms as prediction of the use of ad blocking in online news users - Sánchez-Blanco, Cristina (2020)
Avoiding commercial content while consuming media is not a new phenomenon. The theory recognizes different mechanisms to explain this behavior and the use of advertising blockers can be recognized as an active and conscious behavioral response to this type of content. It is interesting to delve into the reasons that can explain this response by the user. This article analyzes to what extent the use of these ad blocking software is related to conscious attitudes and what is the probability that certain profiles will use them more or less. The case of online news users in Spain is studied with the data from the Digital News Report 2018, which surveyed a representative sample of 2023 Spanish adults. Through a binomial logistic regression, it is shown that some demographic aspects such as age and gender seem to indicate a greater propensity to use this type of online advertising blocking software. Also users with an active attitude are more likely to use programs to block digital advertising. In contrast, it is shown how there are two profiles of people who are less likely to use these software: those who pay for online news and those who have greater familiarity and critical knowledge of the information sector.